Malacosporean myxozoans exploit a diversity of fish hosts. Issue 7 (12th March 2019) - Naldoni, Juliana; Adriano, Edson A.; Hartigan, Ashlie; Sayer, Carl; Okamura, Beth
Abstract: Myxozoans are widespread and common endoparasites of fish with complex life cycles, infecting vertebrate and invertebrate hosts. There are two classes: Myxosporea and Malacosporea. To date about 2500 myxosporean species have been described. By comparison, there are only five described malacosporean species. Malacosporean development in the invertebrate hosts (freshwater bryozoans) has been relatively well studied but is poorly known in fish hosts. Our aim was to investigate the presence and development of malacosporeans infecting a diversity of fish from Brazil, Europe and the USA. We examined kidney from 256 fish belonging variously to the Salmonidae, Cyprinidae, Nemacheilidae, Esocidae, Percidae, Polyodontidae, Serrasalmidae, Cichlidae and Pimelodidae. Malacosporean infections were detected and identified by polymerase chain reaction and small subunit ribosomal DNA sequencing, and the presence of sporogonic stages was evaluated by ultrastructural examination. We found five malacosporean infections in populations of seven European fish species (brown trout, rainbow trout, white fish, dace, roach, gudgeon and stone loach). Ultrastructural analyses revealed sporogonic stages in kidney tubules of three fish species (brown trout, roach and stone loach), providing evidence that fish belonging to at least three families are true hosts. These results expand the range of fish hosts exploited by malacosporeans to complete their life cycle.